Exploring the Gut Microbiome's Influence on Obsessive-Compulsive Disorder: Review of Current Literature - Chmura, Katarzyna; Zygmunt, Natalia; Skubis-Borowiec, Małgorzata; Borowiec, Arnold; Chlubek, Anna; Kleinrok, Jadwiga; Sychta, Szymon; Wąchol, Urszula; Wierzbowska, Patrycja (Quality in Sport, 2025)
Introduction: Obsessive-compulsive disorder (OCD) is a common and disabling neuropsychiatric condition characterized by obsessions and compulsions, significantly impacting quality of life. Current treatments include pharmacological and psychological therapies. However, the exact etiology remains unclear. Growing research highlights the gut-brain axis and the gut microbiome's influence on mental health. Aim of the study: This review aims to examine the existing literature on the interplay between the gut microbiome and OCD, exploring its pathophysiological role and therapeutic implications. Materials and method: An extensive literature search was conducted in the PubMed database up to the year 2025. Conclusions: This review highlights growing evidence of a significant link between the gut microbiome, the gut-brain axis, and obsessive-compulsive disorder. Changes in gut bacteria can impact brain function and contribute to OCD symptoms. While animal studies have confirmed the existence of the microbiota-gut-brain axis and suggested its role in psychiatric disorder pathogenesis, studies on human remain limited. This gap is especially apparent in out understanding of gut microbiota changes in patients with OCD, marking a critical area for future research. Although research is still emerging, microbiome-targeted interventions – such as probiotics, fecal microbiota transplantation (FMT), and dietary changes – show promise, especially for treatment-resistant OCD. To translate these findings into better patient care, we need increased awareness and more large-scale human studies. These efforts may help identify specific microbial profiles and mechanisms, leading to more effective and personalized treatments for OCD.